Evaluasi Program Pembinaan Senam Artistik Menggunakan Pendekatan CIPP - Lusi Angelia; Hendra Jaya; Sri Gusti Handayani; Anton Komaini; Sepriadi Sepriadi; yummi meirafoni; Nadia Fadilla Damayanti (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
The problem of this research is the lack of encouragement and focus on the development of artistic gymnastics in Lima Puluh Kota Regency, which is still below expectations, so that the expected artistic gymnastics coaching and achievements have not been realized. This study aims to evaluate the artistic gymnastics coaching program in Lima Puluh Kota Regency. The method in this study uses a qualitative descriptive approach with the CIPP method (Context, Input, Process, and Product). A total of 9 artistic gymnastics athletes, parents, and all PERSANI administrators became participants in this study. Data were collected through observation, interviews, and documentation. The results of the research on the context have produced results; the program is carried out in accordance with the vision and mission. In terms of input in making training programs, it has not been maximized based only on the experience and thoughts of the trainers; facilities and infrastructure have not been optimal, and the funds and budgets allocated have not been optimal. The process of implementing training programs with physical, technical, and tactical training components is only based on experience, and there is still a lack of management supervision. The product component shows that artistic gymnastics achievements are still running in place. The entire artistic gymnastics coaching program in Lima Puluh Kota Regency needs improvement in terms of context, input, process, and product.